EFEKTIVITAS KEGIATAN WORKSHOP DALAM MENINGKATKAN KEMAMPUAN MENETAPKAN KRITERIA KETUNTASAN MINIMAL (KKM) - I Wayan Sudanta (DHARMASMRTI: Jurnal Ilmu Agama dan Kebudayaan, 2015)
Through the workshop it can be observed that the teacher ability has been increasing in deciding the minimum completeness criterion of the Hinduism teachers in the elementary schools (SD) of the Pejeng cluster, Tampaksiring district, Gianyar regency within the year of study of 2013/2014. The elementary school Hinduism teachers in Pejeng cluster have given a very positive response towards the minimum completeness criterion deciding activity through a workshop. Therefore, the workshop activityhas given a positive impact on the teacher competence in deciding the minimum completeness criterion.